Role of antioxidant to protect Leydig cells induced by reactive oxygen species: a literature review - Anak Agung Istri Dalem Cinthya Riris; Reny I'tishom; Siti Khaerunnisa (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
The Leydig cells play crucial role in steroidogenesis and spermatogenesis. Those processes need complex communication in hormonal and testicular to maintain male reproductive function. Abnormal condition induced by reactive oxygen species reduce cell viability through lipid peroxidation and apoptotic pathway. Antioxidant ameliorate ROS elevation and prevent cell damage. Specifically, Leydig cells are vulnerable to ROS exposure and decline its function in mediating spermatogenesis. Therefore, it is needed to improve Leydig cells viability within antioxidant supplementation. This study aimed to determine the protective effect of antioxidant on Leydig cells induced by reactive oxygen species. This type of study is a literature review. Various studies have been reviewed through critical appraisal tool Olsen-Baisch Scoring for integrated review. Furthermore, this study highlighted the importance of the mechanism of antioxidant as protective agent of Leydig cells. Supplementation of antioxidant with the correct administration, dosage, and duration is potential to balance reactive oxygen species level and protect Leydig cells.    Keywords             : Leydig cell, antioxidant, reactive oxygen species, infertility